Sarcoidosis: Pitfalls and Challenging Mimickers - Narula, Naureen; Iannuzzi, Michael (Frontiers in Medicine, 2021)
Sarcoidosis, a systemic granulomatous disease of unknown etiology, may mimic other conditions at presentation often resulting in delayed diagnosis. These conditions include infections, neoplasms, autoimmune, cardiovascular, and drug-induced diseases. This review highlights the most common sarcoidosis mimics that often lead to pitfalls in diagnosis and delay in appropriate treatment. Prior to invasive testing and initiating immunosuppressants (commonly corticosteroids), it is important to exclude sarcoid mimickers.